EL PROCESO DE NUREMBERG Y EL DERECHO INTERNACIONAL, por Jaime Yrigoyen von der Heyde. - 298 págs. - Talleres Gráficos P. L. Villanueva. - Lima, 1955. - Kiefer Marchand, Xavier (1956)
No contiene resumen